2022
DOI: 10.1007/s11071-022-07395-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of saturated treatments on HIV-TB dual epidemic as a consequence of COVID-19: optimal control with awareness and treatment

Abstract: In this study, we propose an HIV-TB co-infection model by considering the treatment provision limitation induced by recent COVID-19 pandemic that impacts this dual epidemic immensely, assimilating the significance of educational attempts. We analyze the model and its submodels with single infections individually. We obtain the awareness-induced basic reproduction numbers and discuss the global stability of disease-free equilibrium when provision limitation is zero. We observe that the submodels exhibit forward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Quadratic objective functional is considered due to the fact that intervention is non-linear in its nature ( Ndii and Adi, 2021 ). In fact, quadratic control is a common form of an objective functional in an optimal control problem and is frequently used in the literature ( Ndii and Adi, 2021 , Alemneh and Alemu, 2021 , Kim et al., 2018 , Shen et al., 2021 , Majumder et al., 2022 , Zamir et al., 2021 , Omame et al., 2020 , Li and Guo, 2022 ). Thus we have the following objective functional …”
Section: Optimal Controlmentioning
confidence: 99%
“…Quadratic objective functional is considered due to the fact that intervention is non-linear in its nature ( Ndii and Adi, 2021 ). In fact, quadratic control is a common form of an objective functional in an optimal control problem and is frequently used in the literature ( Ndii and Adi, 2021 , Alemneh and Alemu, 2021 , Kim et al., 2018 , Shen et al., 2021 , Majumder et al., 2022 , Zamir et al., 2021 , Omame et al., 2020 , Li and Guo, 2022 ). Thus we have the following objective functional …”
Section: Optimal Controlmentioning
confidence: 99%
“…More recent studies on the mathematical modeling of the COVID-19 pandemic can be found in the Refs. [ 33 – 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies on the mathematical modeling of the COVID-19 pandemic can be found in the Refs. [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%